The influence of service quality, price perception of service and word of mouth on revisit intention in KiosK Padang. - Yulia Yulia; Astri Yuza Sari (Universitas Negeri Padang, 2022)
The purpose of this study was to analyze the influence of service quality, price perception of service and word of mouth on revisit intention in KiosK Padang.. The results of the study are (1) There is a significant and positive effect between service quality and monetary price on KiosK Padang. (2) There is a significant positive effect between service quality on behavior price on KiosK Padang. (3) There is a significant positive effect between the monetary price on word of mouth. (4) There is a significant positive effect between behavior price on word of mouth. (5) There is a significant positive effect between service quality on word of mouth. (6) There is a significant positive effect between word of mouth on revisit intention. (7) There is a significant positive effect between monetary price on revisit intention through word of mouth. (8) There is a significant influence between behavior price on revisit intention through word of mouth